Business ethics practices and programs in Bangladesh: an empirical analysis - Md. Mahi, Uddin (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2015)
Link to publisher's homepage at http://ijbt.unimap.edu.my